First aid assistance for burns for students of Muhammadiyah 1 Senior High School of Pontianak City - Haryanto Haryanto; Lestari Makmuriana; Junaidi Junaidi; Ledy Ervita; Maria Magdalena; Meli Shinta Aristy (Universitas Muhammadiyah Magelang, 2022)
Burns are an emergency problem that can occur anywhere and anytime. An emergency is often a serious and sometimes dangerous situation that occurs suddenly and requires immediate action to save lives. Burns are tissue damage or loss caused by contact with heat sources such as fire, hot water, chemicals, electricity and radiation. Therefore, this activity aims to increase the knowledge of the students of SMA Muhammadiyah 1 Pontianak City in performing first aid on burns and to encourage the active role of students in handling burns. This service uses an action research method with a participatory action program approach. After conducting health education about the first treatment of burns, it was found that there was an increase in students' knowledge and understanding of the first treatment of burns.